Scaling Decision-Support Tools to Promote Soil Health: Insights From Stakeholders in Europe and Turkey - Jouini, M.; Warren Raffa, D.; Delin, S.; Dirnēna, B.; Trinchera, A.; Kasparinskis, R.; Demir, Z.; Baratella, V.; Erdal, Ü.; Räsänen, Timo A.; Hanegraaf, M. (Wiley-Blackwell, 2025)
Soil health and climate change are increasingly impacting agriculture across Europe. Decision support tools (DSTs) have emerged as essential tools to help make accurate, evidence-based agricultural decisions aimed at enhancing productivity, profitability, and effective soil health management. Nevertheless, the adoption of these tools remains limited among farmers and varies across different regions. The aim of this study was to investigate, through a participatory approach, the challenges and drivers influencing the uptake and adoption of DSTs for sustainable soil management in Europe and Turkey. Our goal was to engage various stakeholders to identify the challenges and drivers associated with this process and collaboratively develop actionable recommendations to expand the application of DSTs. Multi-stakeholder workshops were conducted in Italy, Latvia, Sweden and Turkey, bringing together end-users, farmers, advisors, tool developers, researchers and policymakers from diverse agricultural contexts. The discussions during these workshops addressed the current use of DSTs, barriers to adoption, and potential solutions for scaling their use. The findings revealed that the primary barriers to adoption and scaling included costs, tool viability, data complexity, limited access to technical support, compatibility issues and insufficient marketing. To overcome these barriers and enhance the appeal of DSTs to users, stakeholders highlighted the necessity for user-friendly, affordable tools that offer enhanced transparency, real-time information, and adaptability to local farming conditions. Furthermore, stakeholders emphasised the importance of user-driven designs that could stimulate the innovation process and consider the interactions between human and technology. This study emphasises the complexity of adopting and scaling DSTs and the need for considering the local agricultural context. Stakeholder insights were categorised into a set of recommendations such as defining the scope of DSTs application, enhancing capacity building, creating a road map for stakeholders, and considering regional disparities in the participatory implementation process. A systematic, participatory approach is essential for addressing the different dimensions of the DST adoption and scaling process while taking into account regional differences in conditions and user needs.
Keywords: decision-support tools; end-users; implementation; multi-stakeholders workshops; participatory approach; soil management